Aboriginal students in health education programs: a focus on professional identity development - Penfold, Margaret L. (2016)
This thesis examined the experiences of Aboriginal (First Nation, Inuit, Métis) students in health education programs as they proceed through the socialization processes involved in professional identity development. I used mixed methods to access the experiences of Aboriginal students attending professional health education programs (Dentistry, Medicine, Nursing, and Pharmacy) in central and western Canada. The first phase of this study used qualitative interviewing methods, where four superordinate themes emerged capturing the main facets of the experiences of eight participants: cultural congruity, academic and social integration, professional identity development, and meaningful markers of success. The superordinate theme of cultural congruity emerged as a cross cutting theme, in that it touched every other aspect of the overall experiences of these students – creating additional dimensions, challenges, and tensions these students had to navigate. Using quantitative measures I then examined the relationships between academic and social integration, cultural congruity, cultural identity, self-construal, and professional identity development for a larger sample of Aboriginal students. Significant positive relationships were observed for academic and social integration and cultural congruity in relation to professional identity development. If students perceived they belonged in terms of their academic and social experiences they were more likely to report feeling positively identified with their future profession. Similarly, if students perceived there was cultural congruity, they were also more likely to report feeling positively identified with their future profession. Academic integration emerged as a unique predictor, accounting for the majority of the variance in professional identity development. This suggests that although cultural and social factors are important factors shaping the experiences of Aboriginal students in these programs, the role of intrinsic interest in the learning process and program ...